2018
DOI: 10.1080/0142159x.2018.1472373
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate education in anaesthesia, intensive care, pain, and perioperative medicine: The development of a national curriculum framework

Abstract: The framework aims to provide support and guidance for medical schools in the development of competent, well-rounded doctors who are able to provide safe, patient-centered care in all areas of medical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 29 publications
1
22
0
2
Order By: Relevance
“…Cooper and Hutton 1 identified the following possibilities: (1) resuscitation, (2) practical procedures, (3) consent and ethics, (4) rapid history taking and preoperative assessment, (5) pre-admission assessment, (6) acute and chronic pain control, (7) recovery ward experience, (8) fluid balance and clinical pharmacology, and (9) intensive care and the consequences of technological medicine. In the course of preparing a new curriculum framework to guide undergraduate education in anaesthesia, 9 we derived eight domains of anaesthetic and critical care practice, setting out what we believed to be the key capabilities of doctors practising in anaesthesia and related specialties ( Table 1). Some of these overlap with the list published 20 yr ago; others reflect the wider scope of our current work.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Cooper and Hutton 1 identified the following possibilities: (1) resuscitation, (2) practical procedures, (3) consent and ethics, (4) rapid history taking and preoperative assessment, (5) pre-admission assessment, (6) acute and chronic pain control, (7) recovery ward experience, (8) fluid balance and clinical pharmacology, and (9) intensive care and the consequences of technological medicine. In the course of preparing a new curriculum framework to guide undergraduate education in anaesthesia, 9 we derived eight domains of anaesthetic and critical care practice, setting out what we believed to be the key capabilities of doctors practising in anaesthesia and related specialties ( Table 1). Some of these overlap with the list published 20 yr ago; others reflect the wider scope of our current work.…”
mentioning
confidence: 99%
“…We followed an inclusive process of curriculum design, aiming to promote high-level learning amongst students, fully described elsewhere. 9 We conducted telephone interviews with anaesthetic educators at 33 UK medical schools identified from a list held by the Royal College of Anaesthetists. The question prompts were piloted and refined before being used in the interviews proper by one of two members of the project team.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The findings from this study are transferrable to the growing literature on the development of pain education frameworks in various disciplines such as medicine, nursing, and dentistry. [30][31][32] Similarly, Mustafa et al 29 explored the lived experience of chronic pain in immigrant Indian-Canadian women using a phenomenological design. The authors found that immigrant Indian-Canadian women's experiences of pain are influenced by several unique sociocultural factors (e.g., gender roles, work burden, lack of social support), which in turn impact pain expression, openness to treatment, and the consequences of pain on the family.…”
Section: Current Controversiesmentioning
confidence: 99%